The Impact Of International Economic Sanctions On Small And Medium Enterprises In Syria - Dayoub, Muhammad Maan; Ismaiel, Roula Gazi; Aizouki, Lina (Latakia University Journal - Economic and Legal Sciences Series, 2020)
International economic sanctions are used as instruments to put pressure on the government of a particular country for the purposes of political change, but its effects are negatively impacted on the economy and on the livelihood of the entire people. In view of the great effect of the sanctions, the international economic sanctions imposed on Syria in ancient times and recently by international organizations and a number of countries have been studied with the aim of defining and understanding their types and trying to reach an appropriate formula to confront their negative effects. The study also examined the effects and consequences of international sanctions on Syrian macroeconomics, especially on small and medium-sized enterprises, because of their importance in the Syrian economy as the approved projects to solve many problems, the most important of which is the unemployment problem. The composition of GDP and the reduction of the trade balance deficit through the production of export commodities. تستعمل العقوبات الإقتصادية الدولية كأدوات للضغط على حكومة بلد معين لأهداف التغيير السياسي، إلا أن أثارها تنصب سلباً على الإقتصاد وعلى معيشة الشعب بالكامل. ونظراً للأثر الكبير الذي تحدثه العقوبات تم دراسة العقوبات الإقتصادية الدولية التي فرضتُ على سورية قديماً وحديثاً من قبل المنظمات الدولية وعدد من الدول، بهدف تعريفها وفهم أنواعها ومحاولة التوصل إلى صيغة مناسبة لمواجهة آثارها السلبية. تم من خلال هذا البحث دراسة آثار ونتائج العقوبات الدولية على الاقتصاد الكلي السوري وبشكل خاص على المشاريع الصغيرة والمتوسطة، نظراً لأهميتها في الإقتصاد السوري كونها المشاريع المعول عليها لحل العديد من المشاكل أهمها مشكلة البطالة، إضافة إلى دورها في تحقيق النمو الإقتصادي من خلال المساهمة في تكوين الناتج المحلي الإجمالي، وتخفيض العجز في الميزان التجاري عن طريق إنتاج سلع تصديرية.